Providing scientific model of transparency regarding institutional and organizational loyalty with emphasis on the mediating role of organizational trust of employees of Medical Sciences - گل افروز رمضانی; احمد رستگار; نصرت ندیم نژاد (Allameh Tabataba'i University Press, 2017)
Methods: The research method is descriptive - correlation. The study population comprised 630 employees, Zahedan University of Medical Sciences. For this purpose, using a random sample of 187 personal was selected. And responded to self-report questionnaire of Organizational loyalty (the attitude Allen & mayer (1990), the behavioral Zaytaml (1996), Organizational trust and transparency Ravlinz (2008). Results: results showed that the relationship between organizational transparency and organizational loyalty, is affected by organizational trust .The Dimensions (accountability, information sharing and participative) organizational transparency on attitudinal, and behavioral dimensions of organizational loyalty is positive Indirect effect and (secretive) organizational transparency on behavioral and Attitudes aspects of organizational loyalty is negative indirect effect. This means that the dimensions of organizational transparency (accountability, information sharing and participative, secretive) on attitudinal and behavioral dimensions of organizational loyalty have not a direct effect. While indirect effect on the four dimensions of organizational transparency on attitudinal and behavioral dimensions of organizational loyalty is significant. This indicates that the mediating role of organizational trust through transparency and organizational loyalty. Also, the amount of variance explained the fitted model study for dimension Attitudes equal is 0/23 and for dimension behavioral loyalty equal is 0/21.